Eliglustat and cardiac comorbidities in Gaucher disease: a pharmacogenomic approach to safety and efficacy - Ain, Noor Ul; Saith, Armaan; Ruan, Audrey; Yang, Ruhua; Burton, Aaron; Mistry, Pramod K. (Frontiers in Medicine, 2025)
IntroductionGaucher disease (GD), a lysosomal storage disorder, results from the accumulation of glycosphingolipids due to deficient lysosomal glucocerebrosidase activity. This pathological accumulation triggers immune activation, which paradoxically induces UDPglucose ceramide glucosyltransferase (UGCG), further exacerbating the metabolic defect. Eliglustat, a highly specific inhibitor of UGCG, functions as a substrate reduction therapy (SRT) and has demonstrated efficacy in reversing GD manifestations in clinical trials and real-world settings. Despite its established safety profile, preclinical studies have shown that supratherapeutic concentrations of eliglustat can inhibit ion channels involved in cardiac electrophysiology. However, pharmacogenomic-guided dosing ensures therapeutic efficacy while maintaining a wide safety margin, minimizing such risks. Nevertheless, lingering concerns regarding cardiac safety have persisted, particularly in patients with preexisting cardiac comorbidities.MethodsWe report a single-center experience of eliglustat use in 13 patients with type 1 Gaucher disease (GD1) and concurrent cardiac comorbidities. Patients underwent standard cardiac evaluations, including electrocardiogram (EKG) with QTc interval assessment and echocardiogram. Eliglustat dosing was guided by CYP2D6 metabolizer status, and potential drug–drug interactions (DDIs) were carefully monitored.ResultsCardiac comorbidities included prior myocardial infarction (n = 2), aortic stenosis (n = 2), atrial fibrillation (n = 2), Wolff-Parkinson-White syndrome (n = 1), pericarditis (n = 1), premature ventricular complexes (n = 2), severe pulmonary arterial hypertension with right heart strain (n = 1), mitral annular calcification with diastolic dysfunction (n = 1), and mildly prolonged QTc interval (n = 1). No patients experienced arrhythmia, QTc prolongation, or arrhythmia-related symptoms. Treatment discontinuation was not required. All patients achieved expected therapeutic outcomes, as evidenced by serial reductions in glucosylsphingosine (GlcSph) levels and other disease indicators.ConclusionThis study represents the first real-world clinical evidence evaluating Eliglustat’s cardiac safety in a high-risk GD1 population. Unlike prior theoretical concerns derived from in vitro ion channel studies, our findings demonstrate that Eliglustat does not induce clinically significant cardiac events when administered according to pharmacogenomic guidelines. The misinformation regarding Eliglustat’s cardiotoxicity, largely driven by speculative interpretations rather than clinical data, is effectively countered by our findings, which show no significant QT prolongation or arrhythmias over a median treatment duration of 8 years.